Localized Ferroelectric Domains via Laser Poling in Monodomain Calcium Barium Niobate Crystal - Leszek Mateusz Mazur (14778868) (2021)
Tightly focused femtosecond infrared optical pulses are employed to invert spontaneous polarization in the bulk of single–domain ferroelectric calcium barium niobate crystal. Such created localized ferroelectric domains could be arranged in 1D, 2D, and 3D patterns. The fabricated domain structures are subsequently used to demonstrate nonlinear diffraction via transverse second harmonic generation. This work constitutes the first realization of optically induced spatially localized ferroelectric domains in the bulk of a single domain ferroelectric medium and has a potential for applications in nonlinear light processing, frequency conversion, and others. Other Information Published in: Laser & Photonics Reviews License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/lpor.202100088